Konsep Toleransi Antar Umat Beragama Dalam Islam - Aldila Winda Pramita; Meyniar Albina (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
The purpose of this research is to analyse the concept of tolerance between religious people in Islam by using the study of classical and modern texts, such as Al-Qur'an and Hadith, in order to understand how Islamic teachings view religious differences. The research method used is with a library research approach that is descriptive-qualitative by using various references that are relevant to tolerance topics, such as journals, books, and online media, which are used as supporting data that is directly related to the research focus. Based on research results shows that tolerance between religious people in Islam is more than just respecting differences, as well as harmony between religious people. This research is expected to deepen the understanding of the relevance of tolerance between religious people in Islam as a basis for peaceful coexistence in the era of globalisation.